Reducing rates of readmission and development of an outpatient management plan in pulmonary hypertension: lessons from congestive heart failure management. (1st December 2020) - Dolan, Justin; Mandras, Stacy; Mehta, Jinesh P.; Navas, Viviana; Tarver, James; Chakinala, Murali; Rahaghi, Franck
Abstract : Pulmonary hypertension currently has minimal guidelines for outpatient disease management. Congestive heart failure studies, however, have shown effectiveness of disease management plans in reducing all‐cause mortality and all‐cause and congestive heart failure‐related hospital readmissions. Heart failure exacerbation is a common reason for readmission in both pulmonary hypertension and congestive heart failure. Our aim was to review individual studies and comprehensive meta‐analyses to identify effective congestive heart failure interventions that can be used to develop similar disease management plans for pulmonary hypertension. A comprehensive literature review from 1993 to 2019 included original articles, systematic reviews, and meta‐analyses. We reviewed topics of outpatient congestive heart failure interventions to decrease congestive heart failure mortality and readmission and patient management strategies in congestive heart failure. The most studied interventions included case management, multidisciplinary intervention, structured telephone strategy, and tele‐monitoring. Case management showed decreased all‐cause mortality at 12 months, all‐cause readmission at 12 months, and congestive heart failure readmission at 6 and 12 months. Multidisciplinary intervention resulted in decreased all‐cause readmission and congestive heart failure readmission. There was some discrepancy on effectiveness of tele‐monitoring programs in individual studies; however, meta‐analyses suggest tele‐monitoring provided reduced all‐cause mortality and risk of congestive heart failure hospitalization. Structured telephone strategy had similar results to tele‐monitoring including decreased risk of congestive heart failure hospitalization, without effect on mortality. Extrapolating from congestive heart failure data, it seems strategies to improve the health of pulmonary hypertension patients and development of comprehensive care programs should include structured telephone strategy and/or tele‐monitoring, case management strategies, and multidisciplinary interventions.